Retroperitoneal laparoscopic partial adrenalectomy (RLPA) for 20-40 mm nonfunctional adrenal tumors in the day surgery mode - Li, Xuwen; Xi, Haibo; Yu, Yue; Liu, Wei; Zhu, Xiaoping; Gong, Zhixian; Fu, Bin; Wang, Gongxian; Zhou, Xiaochen (Frontiers in Endocrinology, 2022)
Objectives: To investigate the outcome and safety of retroperitoneal laparoscopic partial adrenalectomy in the treatment of nonfunctional unilateral adrenal tumors in the day surgery mode. Methods: Nineteen patients bearing nonfunctional unilateral 20-40 mm adrenal tumors were prospectively enrolled and underwent retroperitoneal laparoscopic partial adrenalectomy in the day surgery unit of our hospital between June 2021 and March 2022. All patients were diagnosed with non-functional adrenal tumors as outpatients before being admitted to the day surgery unit with their consent. Patient demographics and perioperative data were prospectively documented. The patients were followed up by telephone on day 1, 3 and 7 after discharge and followed up for 6 months. Results: The patient’s age was 50.5 ± 11.9 yr (range from 19.0 - 69.0). Seven patients were female. Twelve patients underwent surgery on the left side. The maximal diameter of tumor was 28.3 ± 5.7 mm (20.0 - 40.0 mm). Operation time was 72.1 ± 14.9 min (58.0 - 120.0 min). Mean blood loss was 64.7 ± 50.4 ml (30.0 - 200.0 ml). The gastrointestinal function recovery time was 9.7 ± 2.6 h (6.0 - 16.0 h). Retroperitoneal drainage was removed 24.8 ± 13.3 h (range 18.0 - 72.0) after surgery. Four patients were transferred to the general ward for postoperative management, while others were discharged within 24 hours after surgery. Length of hospital stay was 48.8 ± 13.1 h (38.0 - 85.0h). Hospitalization expense was 24168.4 ±2910.3 RMB￥ (20844.3 - 34369.8 RMB￥). Postoperative pathology revealed 17 cortical adenoma, 1 pheochromocytoma and 1 lymphatic duct tumor. Conclusion: Retroperitoneal laparoscopic partial adrenalectomy for nonfunctional unilateral adrenal tumors in the day surgery mode is safe when strict selection criteria and perioperative management protocol are followed, which has the potential to shorten length of hospital stay and reduce lower hospitalization costs.